Pengaruh Kepentingan Investor, Kreditur, Supplier dan Struktur Modal Terhadap Kualitas Akrual - Gina Nur’alia; Rini Indriani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The quality of accruals is an important indicator in assessing the reliability of a company's financial statements. This study aims to analyze the influence of investors, creditors, suppliers, and capital structure on the quality of accruals in healthcare and transportation & logistics sector companies listed on the IDX for the 2019–2023 period. This study uses a quantitative approach with the purposive sampling method, resulting in 31 companies as a sample with a total of 74 observations of the company's financial statements. Data analysis was carried out using multiple linear regression. The results of the study show that investor interests have a significant effect on the quality of accruals with a significant value of 0.014<0.05. Creditors' interests have a significant effect on the quality of accruals with a significant value of 0.003<0.05. The interests of suppliers have a significant effect on the quality of accruals with a value of 0.00<0.05. Meanwhile, the capital structure did not have a significant effect on the quality of accrual with a value of 0.490>0.05.